(untitled) (Texas Journal of Philology, Culture and History, 2025)
In contemporary society, where globalization, technological advancement, and rapid socioeconomic transformations have reshaped our daily lives, the moral foundations of communities have become more crucial than ever. Among these foundations, honesty, justice, and integrity stand as the cornerstones of ethical behavior and sustainable development. Unfortunately, corruption—manifesting in forms such as bribery, favoritism, and abuse of power—remains one of the most serious obstacles to societal progress. Addressing corruption requires not only legal and administrative reforms but also preventive educational measures that target the roots of unethical behavior. The “Honesty Vaccine” is an innovative educational concept designed to instill immunity against corruption from the earliest stages of human development, starting in preschool education.